Substrates for the tree of seed germination of carmar (Carthamus tinctorius L.) - R. B. Freitas; L. R. Fachi; A. N. Albuquerque (Scientific Electronic Archives, 2018)
The objective of this work was to evaluate the different substrates in the germination potential of safflower seeds. A completely randomized design was used, with five substrates: paper roll, between paper, on paper; Between sand and sand. Seeds of two safflower cultivars were used, with four replicates of 50 seeds each. It was evaluated: percentage of germination (GER); First germination count (GPC); Germination speed index (IVG); Mean germination time (TMG); Percentage of dead seeds (SM); Length of seedling (CP); Root length (CR) and shoot length (CPA). The data were submitted to analysis of variance and the means were compared by the Tukey test, at 5% probability, using the statistical program SISVAR 5.1. It was observed that: the germination (G) of the safflower seeds did not differ between any of the substrates, varying between 77.5% and 85.25%; For the first germination count (PCG), mean germination time (TMG), germination velocity index (IVG) and root length (CR), the best substrates were between paper, paper and sand; And the substrates between paper and sand obtained better results for seedling length and shoot length.